LA AUDICIÓN SUTIL BAJO LAS AGUAS DE LOS CANALES: EL MUNDUS IMAGINALIS EN LA MÚSICA DE LUIGI NONO - Gonzalo Carbó, Antoni (El Azufre Rojo, 2023)
Resumen: El presente artículo analiza la presencia del mundo intermedio o mundo imaginal (ʽālam al-miṯāl), el mundo del malakūt (el mundo del Alma y de las almas) de los grandes gnósticos del islam (Šihāb al-Dīn Yaḥyā Suhrawardī, Muḥyī l-Dīn ibn al-ʽArabī) en la obra de Luigi Nono (1924-1990), uno de los compositores más reputados del siglo XX. Gracias a su lectura de los estudios del pensador e islamólogo francés Henry Corbin, el insigne compositor veneciano concibió la idea de «la Forma imaginal del sonido». Su amistad personal con el filósofo Massimo Cacciari contribuyó a este interés. La imaginación puede entenderse en términos psicológicos (Platón, Aristóteles), o de subjetividad trascendental (como en Kant), o bien como mundo objetivo, mundus imaginalis, susceptible de percepción visionaria, como en la epistemología «oriental» del Islam espiritual, el mundus imaginalis de Suhrawardī o de Ibn al-ʽArabī, interpretado por Henry Corbin y otros importantes estudiosos. Abstract: “The Subtle Hearing under the Waters of the Canals: the Mundus Imaginalis in the Music of Luigi Nono”. This article analyzes the presence of the intermediate world or imaginal world (ʽālam al-miṯāl), the world of malakūt (the world of Soul and souls) of the great Gnostics of Islam (Šihāb al-Dīn Yaḥyā Suhrawardī, Muḥyī l-Dīn ibn al-ʽArabī) in the work of Luigi Nono (1924-1990), one of the most renowned composers of the 20th century. Thanks to his reading of the studies of the French thinker and Islamologist Henry Corbin, the renowned Venetian composer conceived the idea of «the imaginal Form of sound». His personal friendship with the philosopher Massimo Cacciari contributed to this interest. Imagination can be understood in psychological terms (Plato, Aristotle), or of transcendental subjectivity (as in Kant), or as an objective world, mundus imaginalis, susceptible to visionary perception, as in the «oriental» epistemology of spiritual Islam, the mundus imaginalis of Suhrawardī or Ibn al-ʽArabī, interpreted by Henry Corbin and other important scholars.